Microbial analysis of coal polluted soils in the region of Karagandy, Kazakhstan (Experimental biology, 2017)
Microorganisms play a major role in ecological biodegradation processes of soil polluted by coal. Here, we assessed the bacterial diversity in coal-contaminated soil samples .The soils samples were taken from four areas for analyses. In present study we conducted the isolation and characterization of microorganisms from Baizhanov mine soil of Karagandy (KCS), State Natural Forest Reserve “Semey Ormany” pinewood soil (SPS), Dmitrievsky forest soil (DFS) and Rudny Altai pinewood soil (APS) .Twenty-one species of bacteria were isolated from KCS, SPS, DFS and APS soil samples using serial dilution and spread-plate method. Preliminary identification of microorganisms was carried out by culturing on nutrient agar media and Gram staining. Results of total microbial count and morphology characterization showed that both the KCS and SPS share similar microbial communities. Most of studied microorganisms are Gram-positive bacillus, cocci, streptobacillus and diplobacillus bacteria. These results provide some useful information in biodegradation of coal-contaminated soil for the further studies.
Keywords: Coal-contaminated soil, forest soil, pine wood soil, bacterial diversity, biodegradation